2019
DOI: 10.23822/eurannaci.1764-1489.104
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life improvement with allergen immunotherapy treatment in patients with rhinoconjunctivitis in real life conditions. Results of an observational prospective study (ÍCARA)

Abstract: Quality of life improvement with allergen immunotherapy treatment in patients with rhinoconjunctivitis in real life conditions. Results of an observational prospective study (ÍCARA) SummaryObjectives. Evaluate the changes in quality of life of patients with allergic rhinoconjunctivitis (AR), with or without asthma, after one-year treatment with allergen immunotherapy. Methods. This was an observational prospective multicenter study. RQLQ questionnaire and VAS scale to assess treatment satisfaction were used. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
1
8
0
2
Order By: Relevance
“…We also found statistically significant differences in how patients in all subgroups rated their quality M a n u s c r i p t a c c e p t e d f o r p u b l i c a t i o n of life after completing AIT. This finding is well in accordance with reports by other researchers [21].…”
Section: Discussionsupporting
confidence: 94%
“…We also found statistically significant differences in how patients in all subgroups rated their quality M a n u s c r i p t a c c e p t e d f o r p u b l i c a t i o n of life after completing AIT. This finding is well in accordance with reports by other researchers [21].…”
Section: Discussionsupporting
confidence: 94%
“…In this article, an improvement in disease-related quality of life was observed one pollen season after treatment initiation, similar to findings in different clinical trials 14,18,19 and observational studies. 20 These results show that both perennial and bi-weekly pre-co-seasonal schedules, both reaching almost the same cumulative dose at pollen season are effective, thus, stressing the importance of the cumulative dose a patient receives before the pollen season irrespective of treatment schedule.…”
Section: Discussionmentioning
confidence: 67%
“…Another study also stated that the administration of immunotherapy to allergic patients significantly improved their quality of life [ 48 ]. Recent studies also found that giving participants specific immunotherapy can improve their quality of life, which is followed by a decrease in the intensity of allergy recurrence found after the use of immunotherapy [ 49 ]. Immunotherapy has been shown to improve the quality of life of participants by reducing the intensity of allergy symptoms, improving physical condition, and also reducing dependence on drug consumption [ 10 , 42 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also stated that the improvement in symptoms of CRA can be significantly improved with the use of specific immunotherapy [ 42 ]. The use of specific allergy immunotherapy has been shown to shorten the symptoms of CRA, which is usually 14 weeks, can be reduced to 3–4 weeks [ 49 ].…”
Section: Discussionmentioning
confidence: 99%